2019
DOI: 10.1177/2325967119891413
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Anterior Cruciate Ligament Tears in the National Football League: A Case-Control Study

Abstract: Background:Anterior cruciate ligament (ACL) injuries are common in American football players. The risk of subsequent ACL reinjury to either the ipsilateral or the contralateral knee in National Football League (NFL) draftees with a history of successful ACL reconstruction before entering the NFL remains unknown.Hypothesis:NFL athletes with a history of successful ACL reconstruction before being drafted will likely demonstrate increased risk of subsequent ACL injury when compared with a control cohort consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…3 In a review of NFL combine participants with a prior ACL injury, Connor et al found a 25% incidence of a subsequent second ACL injury (12 ipsilateral and 14 contralateral) during their NFL career, which was significantly greater than the incidence of primary ACL injury among a healthy, matched control cohort (18/200 ¼ 9%; P < .001). 7 The results from the present study demonstrated that from a cohort of NFL athletes who played in NFL games prior to their first ACL reconstruction and successfully returned to play for at least half of an NFL season, 28.9% (13/45) sustained a second ACL injury, with approximately equal distribution of reinjury and contralateral injury (54% vs 46%). Although these results show a greater incidence of subsequent injury than prior literature, it is likely secondary to the stringent inclusion criteria applied.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…3 In a review of NFL combine participants with a prior ACL injury, Connor et al found a 25% incidence of a subsequent second ACL injury (12 ipsilateral and 14 contralateral) during their NFL career, which was significantly greater than the incidence of primary ACL injury among a healthy, matched control cohort (18/200 ¼ 9%; P < .001). 7 The results from the present study demonstrated that from a cohort of NFL athletes who played in NFL games prior to their first ACL reconstruction and successfully returned to play for at least half of an NFL season, 28.9% (13/45) sustained a second ACL injury, with approximately equal distribution of reinjury and contralateral injury (54% vs 46%). Although these results show a greater incidence of subsequent injury than prior literature, it is likely secondary to the stringent inclusion criteria applied.…”
Section: Discussionmentioning
confidence: 53%
“…8 Additionally, athletes with a history of ACL reconstruction have a higher likelihood of suffering a contralateral ACL injury. [7][8][9] The work of Paterno et al identified the psychological toll of a primary ACL injury and subsequent reconstruction as a significant factor in increasing the risk of a second ACL tear, 10 while the fear of suffering a reinjury, in turn, places a great psychological toll on athletes as well. 11,12 Given the decrease in average career lifespan of NFL players to approximately 3 seasons, 13 from 4.6 seasons a decade ago, 14 the potential of an ACL injury to negatively affect the longevity and performance of an NFL career can be a concern for athletes and organizations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 It has been reported that among NFL players, ACL reinjury occurs at a rate of 25%, which is notably higher than the reported 11.8% incidence in NBA players. 10,18 Finally, it has been found that although NBA players are reported to reach preinjury baseline performance by the second season after RTP, NFL players exhibit reduced performance for 3 seasons after RTP. 6 These factors contribute to the retained earnings after RTP from ACL reconstruction in NBA athletes.…”
Section: Discussionmentioning
confidence: 98%